2017
DOI: 10.1073/pnas.1619320114
|View full text |Cite
|
Sign up to set email alerts
|

CYCLOPS reveals human transcriptional rhythms in health and disease

Abstract: Circadian rhythms modulate many aspects of physiology. Knowledge of the molecular basis of these rhythms has exploded in the last 20 years. However, most of these data are from model organisms, and translation to clinical practice has been limited. Here, we present an approach to identify molecular rhythms in humans from thousands of unordered expression measurements. Our algorithm, cyclic ordering by periodic structure (CYCLOPS), uses evolutionary conservation and machine learning to identify elliptical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
272
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(277 citation statements)
references
References 48 publications
(42 reference statements)
4
272
0
1
Order By: Relevance
“…S1K, L) [22,25,26]. Reconstructed human lung and liver rhythms similarly show oscillations in CBS expression [27]. Time course microarray studies demonstrate that Cbs expression is reduced in Clock mutant animals and altered circadian rhythmicity ( Fig.…”
Section: Introductionmentioning
confidence: 79%
“…S1K, L) [22,25,26]. Reconstructed human lung and liver rhythms similarly show oscillations in CBS expression [27]. Time course microarray studies demonstrate that Cbs expression is reduced in Clock mutant animals and altered circadian rhythmicity ( Fig.…”
Section: Introductionmentioning
confidence: 79%
“…Anafi et al (30) published CYCLOPS : a neural network that finds circadian patterns in datasets (31). This study does not present an algorithm that can (yet) tell the time of single samples (and does not claim to be able to), but it has clear value in this field.…”
Section: S135 Cyclopsmentioning
confidence: 95%
“…90 The circadian timing system controls several critical molecular pathways for cancer processes and 91 treatment effects. While in the cells of most healthy tissues the cell cycle is gated or phase-locked by the 92 circadian clock (29,30), cancer cells often escape this control and display altered molecular clocks (31-93 33). Dysregulation of clock genes promotes tumorigenesis (25) through mechanisms involving the cell 94 cycle (34,35), DNA damage (36), and metabolism (37).…”
Section: Introduction 50mentioning
confidence: 99%
“…Most clinical samples are collected at time of visit or post-mortem in the extreme case, and the specific time of collection is not always on record. In a recent study [25], a computational tool was reported to assign time series to unordered clinical samples, which revealed dysregulated, but not disrupted, rhythms in hepatocellular carcinoma. This approach can be applied to illuminate circadian rhythms of other clock-related diseases, advancing our understanding of circadian etiology and design of targeted choronomedine.…”
Section: Key Issues To Advance Chronomedicinementioning
confidence: 99%